Review and Certification of Environmental Assessment/Environmental Impact Report for the Oxnard Airport Master Plan - Rodney L. Murphy:::::: (1999)
Various correspondence discussing the Oxnard Airport Master Plan and discussion of the final approval needed. Includes information on the Mitigation Monitoring and Reporting Program for the Oxnard Airport.